Kajian Sistematis tentang Peptida Parenteral: Instabilitas, Mekanisme Degradasi, dan Strategi Formulasinya - Nugrahadi, Primawan Putra; Avanti, Christina (Pengurus Pusat Ikatan Apoteker Indonesia, 2023)
Abstract: The trend of using peptides, short chains of amino acids, as therapeutic agents has been increasing in recent decades. Therapeutic peptides usually use the parenteral route as systemic delivery system, requiring an aqueous formulation. However, in aqueous formulation, peptides are often unstable. The most stable form of therapeutic peptide is a lyophilized powder. Unfortunately, for tropical and developing countries such as Indonesia, as well as from pharmaco-economic point of view, if stable, peptide formulations in aqueous solution are preferred. This systematic literature review provides the various degradation pathways potentially experienced by therapeutic peptides available in Indonesia in aqueous solution. Then present various known strategies to prevent peptide degradation based on recent research. Article were searched on the PubMed, ScienceDirect, Wiley Online Library, and Google Scholar databases. Search results with keywords: therapeutic peptide OR peptide drug AND stability OR stabilization AND degradation OR degradation pathway found 20 articles that met the inclusion and exclusion criteria. Results showed that aggregation is the most common degradation pathway, followed by deamidation, hydrolysis, β-elimination, and disulphide exchange. The main strategies to improve peptide stability in solution are buffer selection and/or pH adjustment, addition of antioxidants/preservatives, combination of buffer with divalent metal ions, avoiding light exposure, and storage in cold temperature.